Morphological characterization of geographical indication litchi crops and released varieties grown in Bangladesh (Bangladesh Journal of Agricultural Research, 2017)
Four Geographical Indication litchi genotypes (GIs) viz., Kadmi Lichu, Mongalbari Lichu, Deshi/Ati/Rajshahi Local (BARI Lichu-1) and Bedana Lichu, and three released varieties viz., BARI Lichu-2, 3 and 4) were characterized morphologically during July 2012 to June 2013 with a view to identifying the degree of morphological and genetic variation of litchi within cultivars, and to establish a permanent database for documentation of litchi. Morphological characterization data were recorded from standing trees of the most concentrated areas of cultivation for GIs and the respective stations from where the variety was released viz., Kadmi from Sonargaon, Narayanganj; Mongalbari from Pakundia, Kishoreganj; Rajshahi Local from Mohanpur village of Shyampur union under Rajshahi district; Bedana from Masimpur, Dinajpur; BARI Lichu-2 and BARI Lichu-3 from RARS, Akbarpur and BARI Lichu-4 from BSPC, Debiganj. Historical background of geographical indication crops of litchi as described by aged people of their most concentrated areas of cultivation indicated that the cultivars were originated naturally in those areas. The cultivars were very location specific. They do not perform well in respect of yield and quality outside their areas of origin indicating their very narrow adaptability range. It was another indication regarding location of origin of the GI crops. On the other hand, the exotic cultivars grown in the country such as BARI Lichu-2, BARI Lichu-3 etc. possess country wide adaptability. Wide variations were observed among the GI crops and released varieties included in this study for plant, leaf, inflorescence, flower and fruit characters. Variation was also recorded in respect of incidence of biotic and abiotic stresses like insect pests, mites, diseases, sunburn, fruit cracking and fruit drop. Each GI/released variety possesses some unique characters, which distinguish it from all other genotypes.Bangladesh J. Agril. Res. 42(1): 103-120, March 2017